2022
DOI: 10.1186/s12883-022-02836-6
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of robot-assisted virtual reality mirror therapy for upper limb motor dysfunction after stroke: study protocol for a single-center randomized controlled clinical trial

Abstract: Background Upper limb motor dysfunction is a common sequela of stroke, and its clinical efficacy needs to be improved. This protocol describes a trial to verify the clinical efficacy of robot-assisted virtual reality mirror therapy (RAVRMT) in improving upper limb motor dysfunction in stroke patients, and to explore the central mechanism by using functional magnetic resonance imaging (fMRI). Methods This trial will be a single-center, assessor-blin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 40 publications
(46 reference statements)
1
7
0
Order By: Relevance
“… 25 , 26 Previous studies have demonstrated the effectiveness of virtual reality-based MT for the upper extremity rehabilitation of stroke survivors. 27 , 28 However, to the best of our knowledge, no study has yet attempted to implement immersive virtual reality-based MT using a 360° camera and HMD that reflects the patient’s own hand in the virtual environment during treatment. For instances, Heinrich et al 29 applied VRMT to upper limb rehabilitation after stroke, testing its feasibility.…”
Section: Discussionmentioning
confidence: 99%
“… 25 , 26 Previous studies have demonstrated the effectiveness of virtual reality-based MT for the upper extremity rehabilitation of stroke survivors. 27 , 28 However, to the best of our knowledge, no study has yet attempted to implement immersive virtual reality-based MT using a 360° camera and HMD that reflects the patient’s own hand in the virtual environment during treatment. For instances, Heinrich et al 29 applied VRMT to upper limb rehabilitation after stroke, testing its feasibility.…”
Section: Discussionmentioning
confidence: 99%
“…So far, diverse clinical trials protocols have been recently developed with the purpose of estimating the motor and functional benefits of RAT and VR-based therapy in different clinical populations [76][77][78][79][80][81][82][83]. Nevertheless, it must be noted that for the most, although factors like patient's mental status or technology acceptance were investigated, these were considered as secondary outcomes essentially.…”
Section: Plos Onementioning
confidence: 99%
“…No conclusions can be drawn to support effectiveness MT for patients in the acute and sub-acute stages. Seven studies (Hung et al 2022); (Wei et al 2022); (Miclaus et al 2021);(Palomo-Carrión et al 2021) (Noureen et al 2022) (Hsieh et al 2020) (Gandhi et al 2020) in this review have included participants in the chronic stage and acute but the majority of them consisted of one lowquality RCT (Wei et al 2022) and 3 experimental studies (Miclaus et al 2021);(Palomo-Carrión et al 2021) (Noureen et al 2022) and two high-quality RCTs (Hung et al 2022) and (Gandhi et al 2020) and 1 high-quality experimental study (Hsieh et al 2020), Furthermore, all case studies used a combination of interventions. Remember the lack of high-quality evidence, it is difficult to conclude that the chronic stage is the optimal time to use this approach.…”
Section: Optimal Time To Start Therapymentioning
confidence: 99%
“…Research result demonstrated that RAT and VRMT are both highly effective for the treatment of improve upper extremity motor dysfunction in stroke patients with activated brain networks associated with movement and circuitry. This is too relevant to the study (Wei et al 2022) The number of samples is 32 people carried out for 4 weeks, with a frequency of once a day and the implementation time is about 20 minutes. The results showed that RAVRMT can improve upper extremity motor dysfunction after stroke better and explored its central mechanism using fMRI.…”
Section: Therapeutic Dose and Degree Of Damagementioning
confidence: 99%
See 1 more Smart Citation